PENGARUH METODE INKUIRI TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA MATERI POKOK EKSPONEN DI KELAS X SMA N 1 BATANG TORU - Fitriani Fitriani (Universitas Islam Sumatera Utara, 2016)
Abstract The background of this research problem is that there are student who are not able to use the properties of exponents and are not able to solve the problems exponent while teaching method used is a meaningful method is the method of inquiry (discovery). The main issues discussed in this study is there any influence on the results of the use of inquiry method of learning mathematics students in the subject matter exponent in class X SMA Negeri 1 Batang Toru. This study aims to explain extent of the influence of the methods of inquiry the math learning outcomes of students in the subject matter exponent in class X SMA Negeri 1 Batang Toru. Calculation of the two variables obtained by the average value of the variable X (inquiry method) is 43.77 are